A PHILOSOPHICAL CHRISTOLOGY OF XAVIER TILLIETTE: Revelation as Kenotic and Reason as Ecstatic - Tritten, Tyler (Science et Esprit)

(untitled) (Collège universitaire dominicain, Ottawa, 2024)
This study has two aims: 1) to provide a concrete instance of how revelation critiques and enlarges philosophy, of how faith dictates to reason, and 2) to draft an outline of a philosophical christology that would fall squarely within the confines of Xavier Tilliette’s own operative principles. Consequently, if revelation is kenotic, then philosophy must also sketch a general ontology that is also kenotic. In other words, if revelation critiques and enlarges philosophy, then kenosis is not exceptional but paradigmatic and so philosophical ontology and philosophical theology must be kenotic all the way down. This article is an attempt to sketch the latter, i.e. a thoroughly kenotic philosophical theology.